The Territory of Our Body: A Conversation on Urban Environments in the Andes and Their Bodies - Solera, Agustina (2023)
Our chapter intertwines dialogically the meanings that flow between the Western and Andean cultural horizons in urban environments marked by coloniality. Attentive to different ways of establishing community, we evoke elements from the Andean cosmovision from a decolonial perspective. By opening to the Andean way of understanding and feeling the relationship between the social and the natural, we rehearse answers to social and environmental crises.